The Disappearance of Objects in "Surmodernity": From Object-images to Meta-objects - Dominique D. Fisher (Studies in 20th & 21st Century Literature, 1996)
This article examines various modes of disappearance of objects from modernity to the latest stage of postmodernity. From the loss of the aura to the proliferation of fractal images, whether it be in literature, contemporary art, or daily life, objects undergo a series of mutations (object-signs, image-objects, object-images, meta-objects) that lead to a new kind of obscenity in which "jouissance" 'pleasure' is released into the madness of a vision obdurated by pathos and panopticism.
Keywords: objects; surmodernity; real objects; imagination; representation; reality